English in Croatia – from needs to achievement - Mihaljević Djigunović, Jelena, Bagarić, Vesna (Array, 2007)
The paper focuses on the aims and research methodology of the Croatian national project English in Croatia. The authors, one of whom headed the research team, point out that reasons for such a project are connected with the need to conceptualise FL education policies on the basis of research-based insights instead of what has been common practice up to now – on unverified individual intuitions. The authors also explain at length the choice of measuring instruments used in the project. They stress that the Hungarian battery of tests used represent measures validated in a similar socio-educational context, that they make possible comparative studies of the same phenomena and that the communicative tests in the battery, aiming at the CEFR A2 and B1 levels, coincide with the language communicative competence set out by the Croational national curriculum. The paper offers a detailed description of the piloting of all the instruments used. Besides the new insights about the status of English in Croatia, the authors also draw attention to some additional project results concerning development of new research competences in the field of FL education investigations.